Flood Syndrome and Portal Vein Thrombosis: An Unusual Complication of Liver Cirrhosis - Abu Fahad Abbasi; Paul Hong; Aleksandra Marinkovic; Adekunle Sanyaolu; Ikponmwosa Enofe (Case Reports in Clinical Practice, 2023)
Spontaneous paracentesis is a life-threatening complication of liver cirrhosis. Importance of precise and early identification cannot be overstated, as early treatment improves the prognosis and survival. A 78-year-old woman with cirrhosis presented with ascitic fluid gushing out from an umbilical hernia. The patient received intravascular repletion with intravenous albumin, antibiotics, and rapid umbilical herniorrhaphy. Post-operatively, the patient experienced acute kidney injury and portal vein thrombosis, which was corrected with electrolyte replacement and transjugular intrahepatic portosystemic shunt with thrombectomy. The patient recovered completely and was discharged without difficulty.